2020
DOI: 10.1093/gigascience/giaa008
|View full text |Cite
|
Sign up to set email alerts
|

GC bias affects genomic and metagenomic reconstructions, underrepresenting GC-poor organisms

Abstract: Background Metagenomic sequencing is a well-established tool in the modern biosciences. While it promises unparalleled insights into the genetic content of the biological samples studied, conclusions drawn are at risk from biases inherent to the DNA sequencing methods, including inaccurate abundance estimates as a function of genomic guanine-cytosine (GC) contents. Results We explored such GC biases across many commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 37 publications
7
85
2
Order By: Relevance
“…Specifically, the abundance of each species differs among the methods. In addition to the presence of unculturable bacteria in the sequencing data, these differences could result from several biases in DNA extraction, PCR efficiency, primer selection, GC content, and data analyses, all of which have been investigated among various sequencing platforms [ 36 , 45 , 46 , 47 , 48 ]. In addition, the impact of bioinformatic methods used to achieve final results is well characterized.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the abundance of each species differs among the methods. In addition to the presence of unculturable bacteria in the sequencing data, these differences could result from several biases in DNA extraction, PCR efficiency, primer selection, GC content, and data analyses, all of which have been investigated among various sequencing platforms [ 36 , 45 , 46 , 47 , 48 ]. In addition, the impact of bioinformatic methods used to achieve final results is well characterized.…”
Section: Resultsmentioning
confidence: 99%
“…The species of the samples is indicated. Tyler et al, 2016;Grützke et al, 2019;Sato et al, 2019;Uelze et al, 2019;Browne et al, 2020) (also compare Supplementary File S7). This is a concern since a high number of contigs in a genome assembly may cause a fragmentation of genes at the contig borders, thereby affecting gene annotation and multilocus sequence typing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that all assemblies were overall very similar, with respect to assembly length, N50, GC and the number of CDSs, with a few notable exceptions. In particular, assemblies constructed from short read data of laboratories LC06 and LC08 (both using a MiSeq Illumina instrument) had much lower N50 values and a greater number of contigs, probably due to their use of the Nextera XT DNA Library Preparation Kit, which was shown to have a strong GC bias ( Lan et al, 2015 ; Tyler et al, 2016 ; Grützke et al, 2019 ; Sato et al, 2019 ; Uelze et al, 2019 ; Browne et al, 2020 ) (also compare Supplementary File S7 ). This is a concern since a high number of contigs in a genome assembly may cause a fragmentation of genes at the contig borders, thereby affecting gene annotation and multilocus sequence typing.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, these observations could be interesting in terms of bone degradation, however, while amplicon metabarcoding has its clear advantages being both cost effective, fast and used in a variety of studies making the genetic databases available more exhaustive, the approach still has its disadvantages [ 32 ]. With the advancement of full shotgun metagenomic sequencing techniques, the sequence bias experienced with amplicon sequencing and issues of underrepresentation of uncultivable microorganisms in the databases, and therefore difficulties in characterisation, is reduced [ 70 ], although shotgun sequencing has recently been found to underrepresent low or high GC phyla with up to two logs [ 71 ]. A natural next step with this study would be to look into the functions of the different bacterial strains and examine how the bacterial communities are associated with bone tunneling using a shotgun metagenomics approach.…”
Section: Discussionmentioning
confidence: 99%